MARKETING STRATEGY IN INCREASING SALES VOLUME OF RAJAWALI MOTOR SHOWROOM CARS - Dian Sudiatini; Chayani Farhanah Putri; Gita Atya Turohmah; Jalu Elang Ageng (Nindikayla Institute, 2023)
Rajawali motor is one of them by buying used goods, which are more affordable but the quality is still good, currently the growing used goods business is buying and selling used cars. The research method is one way to search, obtain, collect, and record data, both in the form of primary and secondary used for the purposes of compiling a scientific paper, In this research was conducted to find out and analyze marketing strategies through SWOT analysis. The marketing strategy carried out by the Rajawali Mobil Showroom, namely by carrying out a marketing mix strategy (Marketing mix) is the main point carried out by the company to achieve its marketing goals in increasing sales volume